PTH-078 A Prospective Evaluation of the Predictive Value of Faecal Calprotectin in Quiescent Crohn'S Disease. (4th June 2013) - Smith, L A; Naismith, G; Barry, S; Munro, J I; Laird, S; Rankin, K; Morris, J; Winter, J W; Gaya, D R
Abstract : Introduction: Studies have suggested that faecal calprotectin (FC) levels may increase early in inflammatory bowel disease relapse before the patient is symptomatic and thus may be useful to identify patients at a higher risk of relapsing. The purpose of this study was to evaluate the role of FC in predicting relapse in patients followed up for a minimum of 12 months and to ascertain the best cut-off for this in our cohort of adult patients with quiescent Crohn's disease (CD). Methods: Patients with CD in clinical remission were recruited and followed up prospectively for a minimum of 12 months. Participants provided stool for FC concentration analysis and the study was terminated once the last recruited patient reached a follow up period of 365 days. Remission was defined as a Crohn's disease activity index (CDAI) of < 150. Relapse was defined as either a need for escalation of medical therapy, surgery for active CD or progression of disease phenotype using the Montreal classification. The study was approved by the West of Scotland Research Ethics Service (REC reference 10/S0704/1). The Receiver Operating Characteristic (ROC) curve of relapse by 12 months, based on FC value at baseline, was calculated. Kaplan-Meier curves of time to relapse, some of which were longer than 12 months, were based on the resulting best FC cut-off value for predicting relapse (with patients who had not relapsed being censored at end of follow-up) and compared using the log-rank tests. Results: 98 patients were recruited. One patient was lost to follow up, 1 died and the care of 3 patients was transferred to another centre, before either relapsing or being followed up for 12 months. Of the 93 remaining patients 11 (12%) had relapsed by 12 months. The median FC was lower for non-relapsers, 96 µg/g (IQR 39–237), than for relapsers, 328 µg/g (IQR 189–574), (p = 0.008). The area under the ROC curve to predict relapse using FC was 74.8% (Figure 1). A cut-off FC value of 240 µg/g to predict relapse of quiescent Crohn's disease over the course of one year was associated with a sensitivity of 72.7% and specificity of 74.3%. Negative predictive value was high at 95.3% and positive predictive value was 27.6%.There was a significant difference in time to relapse for those with the first FC value below or above 240 µg/g (p = 0.011). Conclusion: In this prospective dataset, FC appears to be a useful, non-invasive tool to help identify quiescent Crohn's disease patients at a low risk of relapse over the ensuing 12 months. A FC value of 240 µg/g was deemed the best cut-off value in our patients. Disclosure of Interest: None Declared.